Assessment of Parents Knowledge, Attitude and Practice about Child Vaccination in Selected Rural Areas of Kalaburagi District, India - Sandeep, S; Biradar, S S; Veeresh, Veeresh (Journal of Drug Delivery and Therapeutics, 2024)
Objective: Immunization has evolved as one of the most successful public health interventions, reducing the incidence of infectious diseases and improving quality of life. This study was conducted to analyze the level of knowledge, attitude and experience of childhood vaccination among local participants from selected rural areas of Kalaburagi District, which can be related to the immunization status of their children.Method: The Prospective, Cross-Sectional study was conducted at selected villages of rural areas in Kalaburagi district. Parents were enrolled into the study by considering the study criteria. Demographic details and other relevant data were collected at pre-test and post-testResults: A total of 631 parents from 10 selected rural areas were enrolled in the study out of which 611 parents completed the study and 20 parents did not complete the study. It was evident that 470(76.92%) children’s immunization was completed according to schedule, 73(11.95%) children’s immunization was not complete according to schedule and 68(11.13%) parents did not know whether child immunization was complete according to schedule or not. The pre and post-test KAP score was assessed using SPSS software and Chi- Square test was carried out to analyze the Statistical significance. The study was statistically significant at p-value of